2013
DOI: 10.1088/0004-637x/777/2/136
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Burning on Accreting White Dwarfs: Stability, Recurrent Novae, and the Post-Nova Supersoft Phase

Abstract: We examine the properties of white dwarfs (WDs) accreting hydrogen-rich matter in and near the stable burning regime of accretion rates as modeled by time-dependent calculations done with Modules for Experiments in Stellar Astrophysics (MESA). We report the stability boundary for WDs of masses between 0.51 M and 1.34 M as found via time-dependent calculations. We also examine recurrent novae that are accreting at rates close to, but below, the stable burning limit and report their recurrence times. Our dense g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
326
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(365 citation statements)
references
References 46 publications
(125 reference statements)
25
326
0
Order By: Relevance
“…All these estimates rely on the assumption of steady state burning. Wolf et al (2013) define steady state burning as stable when an increase in temperature causes the cooling rate to increase more than the energy generation rate. In their models, the lower limit for steady state burning is 3.8 × 10 −7 M⊙yr −1 for a 1.34M⊙ WD and lower for less massive WDs.…”
Section: Three Candidate Pre-snmentioning
confidence: 99%
“…All these estimates rely on the assumption of steady state burning. Wolf et al (2013) define steady state burning as stable when an increase in temperature causes the cooling rate to increase more than the energy generation rate. In their models, the lower limit for steady state burning is 3.8 × 10 −7 M⊙yr −1 for a 1.34M⊙ WD and lower for less massive WDs.…”
Section: Three Candidate Pre-snmentioning
confidence: 99%
“…The agreement is quite good even between authors drawing opposite conclusions regarding the existence of the stability strip. In the parameter range of interest, there is a good agreement between analytical (Fujimoto 1982) and more sophisticated numerical calculations, as well as between single flash (Fujimoto 1982;Starrfield 2014) and multicycle (Yaron et al 2005;Wolf et al 2013) calculations. We note that the latter two probably provide a more accurate representation of the accreting WD, and their results agree to much better than a factor of ∼2.…”
Section: Discussionmentioning
confidence: 66%
“…In the classical picture, copious amounts of material are lost in the nova explosion, especially at the lower mass-accretion rates (Ṁ < ∼ 10 −7 −10 −8 M yr −1 in the Yaron et al 2005 calculations, for example), rendering the growth of the WD mass impossible or insignificant in the context of SN Ia progenitors. Importantly, several authors have found that the transition from unstable to stable burning is sharp -there is a discontinuity in the stability of burning, with the large amplitude flashes occurring very close to the stability strip (e.g., Wolf et al 2013;Kato et al 2014). However, the main aspects of this picture have been contested by several authors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations